Translating media texts in multilingual settings - Satibaldiev, Erkinjon (The Lingua Spectrum, 2025)
In an era marked by global connectivity, media texts often traverse multiple linguistic and cultural boundaries. This circumstance has elevated the importance of translation as a tool for effective intercultural communication. Specifically, translating media content between English, Russian, and Uzbek requires a nuanced understanding of pragmatic meaning and the influence of language dominance. This article offers a comprehensive analysis of existing literature on the translation of media texts across these three languages, focusing on pragmatic challenges, the role of English as a global lingua franca, cultural and linguistic specificities, and recommended translation strategies. Drawing on key theoretical and empirical works – including foundational studies in translation theory, pragmatics, and multilingual education – this discussion illuminates how language dominance and pragmatic features shape translational decisions. The findings highlight the necessity of balancing linguistic accuracy with cultural adaptability to preserve communicative intent. Ultimately, this article emphasizes that meeting pragmatic equivalence in cross-linguistic media translation demands rigorous awareness of socio-cultural norms, language hierarchies, and audience expectations.